Assessment of the environmental analysis process and the development of a mapping methodology for industrial zoning : case study of Batangas Province, Philippines - Bloxom, Lonela Jimenez; Lukens, John E.; Robinson, Ira. M.; Verink, Johan; Canadian International Development Agency (CIDA) (Bangkok : Asian Institute of Technology, 1990)
A major problem facing many Third World countries is the potential adverse effects of industrial development. This problem has arisen, partially because of the lack of readily available and applicable analytical techniques to identify these negative effects in the initial planning stages of industrial development projects. Since most Third World countries cannot afford expensive curative approaches for environmental problems, this thesis is of value, in that it provides a preventive planning approach to overcome the above problem. Proper environmental analysis and planning in the earl y stages of industrial development can pay high returns in the future if costly curative measures can be avoided. This study, focusing on a proposed industrial development project in the Batangas Province of the Philippines, demonstrates the application of a comprehensive environmental analysis framework through the use of a computer-based Geographic Information System to : a) Compile an environmental information data base b) Identify suitable sites for industrial development c) Identify potential conflicts and problems between industrial development and the environment The framework developed in this stud y could be a useful planning tool for the site selection of industrial development projects in t he Third World .
A thesis submitted in partial fulfillment of the requirements for the degree of Master of ·Science, School of Environment, Resources and Engineering
Thesis (M.Sc.) - Asian Institute of Technology, 1990
Keywords: Philippines -- Industries -- Location -- Environmental aspects